POLYMER SCREENING TO IMPROVE ACID SWEEP EFFICIENCY IN URANIUM ISR PROCESS - Veintimilla Vela, Santiago David (School of Mining and Geosciences, 2023)
In-situ leaching (ISL) is a widely used technique for the extraction of uranium from ore bodies. The ISL process involves the injection of a leaching solution into the ore body through wells drilled into the formation. The leaching solution dissolves the uranium from the ore, and the resulting solution is then pumped to the surface for processing. One of the main challenges in the ISL process is the heterogeneity and anisotropy in the petrophysical properties of the reservoir. The ore body may contain multiple zones with varying permeability values and a constant porosity value making it difficult for the acidic solution to reach the main objective zones for production. As a result, a large volume of acidic solution is often injected to ensure that the solution reaches the targeted zones by density differentiation. However, this solution leads to a higher volume of injection solution needed, and the operational costs of the process become prohibitive. This study attempts to provide a new direction in the production of uranium through the ISR process and a practical solution to improve acidic solution use and enhance its sweep efficiency by the use of polymer flooding. The aim of this study is to screen the performance of different polymers to identify the most effective ones in enhancing sweep efficiency. The study investigates the effects of polymer concentration on the viscosity of the polymer on the surface of the ore. The use of polymers can enhance the viscosity of the acidic solution, reduce the heterogeneity between the layers on the reservoir and displace the desired resulting solution as uniform as it can be. The results of polymer screening will provide data to a simulation of polymer flooding under determined parameters. The main objective of this simulation is to demonstrate that polymer can enhance the sweep efficiency of the injected fluid even being under extreme conditions as low pH values, enabling it to reach the main objective zones for production. This can reduce the operational costs of the process and increase the sustainability of uranium extraction from ore bodies. As a result the sweep efficiency was improved from 0.72 in the first case scenario, only acidic solution injection, to 0.80 after polymer flooding. Furthermore, the study can contribute to the understanding of the mechanisms of polymer flooding in the ISL process, providing a foundation for further research on this topic.
Keywords: Type of access: Restricted; In-situ leaching; Polymer screening; uranium ISR process; acid sweep efficiency